2017
DOI: 10.1111/1753-6405.12686
|View full text |Cite
|
Sign up to set email alerts
|

Farm injury hospitalisations in New South Wales (2010 to 2014)

Abstract: Objective: To examine gender differences in the characteristics, treatment costs and health outcomes of farm injuries resulting in hospitalisation of New South Wales (NSW) residents. Method: A population‐based study of individuals injured on a farm and admitted to hospital using linked hospital admission and mortality records from 1 January 2010 to 30 June 2014 in NSW. Health outcomes, including injury severity, hospital length of stay (LOS), 28‐day readmission and 30‐day mortality were examined by gender. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Overall, about one-third of agricultural accidents involved the upper extremity ( Figure 3) [6]. As reported also in the international literature, upper limb's injuries occurring in the farm environment can be very serious, resulting in a relevant loss of working days, often leading to amputation of at least one finger and sometimes to permanent disability [7][8][9]. In this scenario, sustainability in agriculture must be considered as a key factor for its development, with the major climate changes and the challenges of the global market [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, about one-third of agricultural accidents involved the upper extremity ( Figure 3) [6]. As reported also in the international literature, upper limb's injuries occurring in the farm environment can be very serious, resulting in a relevant loss of working days, often leading to amputation of at least one finger and sometimes to permanent disability [7][8][9]. In this scenario, sustainability in agriculture must be considered as a key factor for its development, with the major climate changes and the challenges of the global market [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, about one-third of agricultural accidents involved the upper extremity ( Figure 3) [6]. As reported also in the international literature, upper limb's injuries occurring in the farm environment can be very serious, resulting in a relevant loss of working days, often leading to amputation of at least one finger and sometimes to permanent disability [7][8][9]. In 2018, the hands were the most affected body part, which sustained an injury (20.5%), followed by the ankle (11.5%), knee (10.7%), wrist (4.7%), eyes (4.6%), foot (4.3%), and elbow (2.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings around farming-related injuries confirm those from international studies, in terms of the most common mechanisms for injury being agricultural machinery (including vehicles), interaction with livestock and falls. 3,7,8,[17][18][19][20][21][22] Our study has identified some high-risk mechanisms for injury, regardless of whether individuals were undertaking a farming activity or not. In summary, some of the key risks in the Midland region are for:…”
Section: Discussionmentioning
confidence: 83%
“…Since the 1980s, children on farms have been recognised in academic literature as a population that is particularly vulnerable to farm-related injury [ 38 ]. Despite research mentioning child farm-related non-fatal injuries [ 39 , 40 , 41 ], there is yet to be comprehensive research examining this in Australia. To date, most non-fatal injury research has concentrated on the state of New South Wales, limiting its validity (and the validity of proposed prevention measures) across the wider Australian context.…”
Section: Resultsmentioning
confidence: 99%